Influence of Internal Quality of Gear on Strength and Life of Gear - Xiaolu Zhu (Jixie chuandong)
The internal quality of gear is determined by material quality， forging quality and heat treatment process quality. Failure of about 35% of the gears is related to their poor internal quality. The influence of some items of internal quality of carburizing quenching gear （surface decarburization， internal oxidation， coarse martensite， carbide structure， non-martensite structure， black structure， retained austenite， grain size， etc.） on gear strength and life are mainly discussed， the degree of influence is mostly expressed by the data of experimental results. Finally， the R-S-N curve test data（gear decarburization layer depth 0.2~0.3 mm， the bending endurance limit stress σF lim at tooth root is reduced by 23%~50%） of carburizing and quenching gears with 5 materials show that the great influence of gear surface decarburization on gear bending fatigue strength.